2020
DOI: 10.14740/cr1034
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and Cardiovascular Disease: A Focused Review on the Impact of Hyperthyroidism in Heart Failure

Abstract: The association between thyroid hormones and cardiovascular conditions has been well studied, specifically, the effects of hypothyroidism on cardiomyopathy, and hyperthyroidism with arrhythmias. Nonetheless, an explicit correlation between hyperthyroidism and cardiomyopathy has yet to be established. Medical databases MEDLINE and PubMed were accessed and queried as primary sources for data acquisition. Search criteria consisted of "hyperthyroidism", "heart failure", and "thyroid and cardiovascular system", whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 50 publications
0
43
2
2
Order By: Relevance
“…Several authors have observed an association between the CV system and the thyroid diseases, but few studies have assessed the correlation between hypothyroidism and cardiac pathologies, with the exception of atrial fibrillation and tachyarrhythmias [ 55 , 56 , 57 , 58 ]. The SMC, as modulators of vascular tone, are a fundamental target for the action of TH [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have observed an association between the CV system and the thyroid diseases, but few studies have assessed the correlation between hypothyroidism and cardiac pathologies, with the exception of atrial fibrillation and tachyarrhythmias [ 55 , 56 , 57 , 58 ]. The SMC, as modulators of vascular tone, are a fundamental target for the action of TH [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, Carrillo-Sepulveda, et al also demonstrated that T 3 causes nitric oxide (NO)-dependent rapid relaxation of vascular SMC by activation of PI3K/Akt-mediated endothelial nitric oxide synthase signaling pathway [ 67 ]. Consequently, recent epidemiological studies have shown that patients with hypothyroidism or with subclinical hypothyroidism may develop increased diastolic blood pressure, probably via decreased endothelium-mediated relaxation and vascular compliance [ 55 , 62 , 68 ]. In this sense, some studies suggested that this vasodilation is a result of the T 3 effects on the PI3K/Akt pathway mediated by non-genomic and genomic actions [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones, especially the bioactive component T3, are closely related to cardiovascular diseases and are essential for cardiovascular diseases, which affect various functions of the heart, including cardiac contractility and electrophysiological remodeling. 1 The mechanisms of T3 5 Hypothyroidism is known to be related with several ECG abnormalities including sinus bradycardia, prolonged QT interval, low voltage, prolonged the action potential duration of cardiomyocytes and heart block at varying degrees. 2 Cardiac K+ and L-type Ca++ channels in patients with hypothyroidism are affected by serum T3 and as a result, ventricular repolarization anomalies develop, which is one of the reasons why hypothyroidism patients have been reported to have an increased risk of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones, especially the bioactive component T3, are closely related to cardiovascular diseases and are essential for cardiovascular diseases, which affect various functions of the heart, including cardiac contractility and electrophysiological remodeling. 1 The mechanisms of T3 on cardiovascular system are diverse, mainly including the following integral aspects: 1. Binding to nuclear T3 receptors that affect the regulation of structure, contraction and gene expression; 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation